Empress of all seasons - Jean, Emiko (Houghton Mifflin Harcourt, 2018)
During a once-in-a-generation competition to find the new empress, Mari, who hides a terrible secret, Taro, the prince who would denounce the imperial throne, and Akira, a half-human outcast, will decide the fate of Honoku.